Identification of Critical Residues for Ligand Binding in the Integrin β3 I-domain by Site-directed Mutagenesis - Yamanouchi, Jun; Hato, Takaaki; Tamura, Tatsushiro; Fujita, Shigeru (Thrombosis and Haemostasis, 2002)
To define the structural basis of ligand recognition by αIIb β3, we conducted site-directed mutagenesis of residues located on the top surface of the β3 I-domain that is homologous to the I-domain of several α subunits and contains a putative ligand binding site. Here we identify D158 and N215 in β3 as novel residues critical for ligand binding. Alanine substitution of D158 or N215 abolished binding of a ligand-mimetic antibody and fibrinogen to αIIb β3 induced by different types of integrin activation. CHO cells expressing recombinant αIIb β3 bearing D158A or N215A mutation did not adhere to fibrinogen. These mutations had the same effect on ligand binding to another β3 integrin, αV β3. Compared to the αI-domain structure, the βB-βC loop containing D158 in the β3 I-domain is quite different in length and sequence. These results suggest that the structure for ligand recognition is different in the βI- and αI-domains.
Keywords: Integrin; αIIb β3; MIDAS; ligand binding site; mutation